2020
DOI: 10.3390/diagnostics10020062
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Evaluation Using Two-Dimensional Speckle-Tracking Echocardiography and Conventional Echocardiography in Taiwanese Patients with Mucopolysaccharidoses

Abstract: Background: Mucopolysaccharidoses (MPSs) are a group of rare inherited metabolic disorders that can damage various organs, including the heart. Cardiac abnormalities have been observed in patients with all MPS types, with the most documented abnormalities being cardiac valvular regurgitation and stenosis, valvular thickening, and hypertrophic cardiomyopathy. Methods: Cardiac features of 53 Taiwanese patients with MPS (31 men and 22 women; age range 1.1–34.9 years; seven with MPS I, 16 with MPS II, nine with MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
9
0
2
Order By: Relevance
“…Typically, LV hypertrophy and diastolic dysfunction occur in the early phases, while LV dilation and systolic dysfunction are common in the final disease stage. Moreover, coronary artery disease and systemic hypertension are common in patients with MPSs and have been associated with the diffuse intimal proliferation from GAG deposition, while electrophysiological anomalies such as atrioventricular blocks are related to fibrosis of the conduction system ( 128 , 131 , 132 ).…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%
“…Typically, LV hypertrophy and diastolic dysfunction occur in the early phases, while LV dilation and systolic dysfunction are common in the final disease stage. Moreover, coronary artery disease and systemic hypertension are common in patients with MPSs and have been associated with the diffuse intimal proliferation from GAG deposition, while electrophysiological anomalies such as atrioventricular blocks are related to fibrosis of the conduction system ( 128 , 131 , 132 ).…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%
“…Patients with MPS IVA manifest features such as waddling gait, abnormal skeletal development, genu valgum (knock knees), bell-shaped chest, joint hypermobility and laxity, spinal deformities, large elbows and wrists, and short stature for their age with a short neck. Moreover, mild hepatosplenomegaly, hearing impairment, respiratory compromise, abnormal heart development, corneal clouding, and deficient tooth enamel may be present [ 9 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, due to macroglossia, temporomandibular joint stiffness, abnormal laryngeal anatomy, trachea deformity, and glottic narrowing predisposes the patients toward difficult and failed intubations, thereby putting such patients at a greater anesthetic risk [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aortic root dilatation is frequently observed in animal models of MPS I, leading to the effacement of the sinotubular ridge [ 8 ]. Some studies have reported that aortic root dilatation may appear in various types of MPS patients, especially in those with MPS IVA [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%